Analysis of Factors Influencing Drug Prices Differently in Official Drug Pricing and Cost-Effectiveness Evaluation - Mariko Hara; Hiroshi Nakamura (Journal of Market Access & Health Policy, 2026)
Background: In Japan, official prices of pharmaceuticals have been determined by efficacy and safety. In 2019, Cost-Effectiveness Evaluation (CEE) was introduced to adjust these prices according to Incremental Cost-Effectiveness Ratios (ICERs). Objectives: To analyze the differences in the factors influencing drug price between the initial official drug pricing and subsequent price adjustments based on CEE. Methods: Twenty-three drugs evaluated in Japan between 2019 and May 2025 were descriptively analyzed using public reports on official drug pricing and CEE. Results: Four differences were identified: (1) Official initial drug pricing grants premiums for certain characteristics that are not directly associated with improvements in Health-Related Quality of Life (HRQoL), whereas such premiums are not considered in CEE. (2) Official drug pricing limits comparators to existing drugs, whereas CEE did not impose such restrictions. (3) Official drug pricing excludes older drugs as comparators to reward innovation, whereas they were not excluded in CEE. (4) CEE requires sufficient data for CE analysis, such as clinical trial or real-world data, for comparators, unlike official drug pricing. Factors (1) and (3) were most frequent. Conclusion: Reducing these differences and maintaining consistent innovation evaluations may enhance price predictability and support sustainable pharmaceutical investments in the Japanese market.